The Moderating Role of Sukuk Rating in the Relationship Between Financial Indicators and Corporate Sukuk Yield - Nurul Rachmaini; Melzatia Shinta; Nurhasanah Nurhasanah; Mohd ‘Adli Zahri (Universitas Mercu Buana, 2022)
As an investment and financing vehicle, Sukuk plays a significant role in Indonesia, which are predominantly Muslim, to address the demand for sharia-based investment and financing instruments. However, the gap between Sukuk and Bonds is still very large, as the development of Sukuk is far less than that of Bonds. This causes investors and issuers to examine the viability of their Sukuk investments, particularly in terms of the risks they undertake and the amount of return they receive. This study aims to assess the impact of financial parameters on the yield of Corporate Sukuk, with rating serving as a moderating variable. This study makes use of quantitative secondary data. The sample consists of enterprises with outstanding Sukuk from 2015 to 2020. The findings of this study demonstrate that liquidity, solvency, and profitability have little effect on the yield of Corporate Sukuk before or after rating moderating. Even though the rating has a substantial negative impact on yield, it cannot alter the impact of financial ratios on yield.